The atomistic details of the ice recrystallisation inhibition activity of PVA - Fabienne Bachtiger (Nature Portfolio, 2021)
Understanding ice re-crystallization is key to improve the current cryopreservation technologies. Here, the authors bring together experiments and simulations to unravel the atomistic details of the ice re-crystallization inhibition (IRI) activity of poly(vinyl)alcohol—the most potent biomimetic IRI agent.